2012
DOI: 10.1002/cbic.201200228
|View full text |Cite
|
Sign up to set email alerts
|

Precursor‐Directed Syntheses and Biological Evaluation of New Elansolid Derivatives

Abstract: The antibiotic elansolid C1 (8) was isolated from Chitinophaga sancti strain FxGBF13 after fermentation in the presence of anthranilic acid. Remarkably, 8 was also obtained by addition of anthranilic acid to a crude fermentation extract containing the macrolide elansolid A2 (1*). This Michael-type conjugate addition allowed us to generate 21 new derivatives of elansolid C1 (9-29) by using various nucleophiles. Biological activities of all derivatives were evaluated against Staphylococcus aureus, Micrococcus lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 10 publications
1
42
0
Order By: Relevance
“…This excellent facial selectivity has been demonstrated, e.g., for anilines as nucleophiles before. It is due to the preferred conformation around the bond at C24–C25 which leads to the efficient shielding of the si -face by the two germinal methyl groups at C22 [45]. The NMR data determined for both synthetic products were identical with those of authentic samples of elansolid B1 ( 2 ) and elansolid B2 ( 3 ) (copies of spectra, see Supporting Information File 1).…”
Section: Resultsmentioning
confidence: 79%
“…This excellent facial selectivity has been demonstrated, e.g., for anilines as nucleophiles before. It is due to the preferred conformation around the bond at C24–C25 which leads to the efficient shielding of the si -face by the two germinal methyl groups at C22 [45]. The NMR data determined for both synthetic products were identical with those of authentic samples of elansolid B1 ( 2 ) and elansolid B2 ( 3 ) (copies of spectra, see Supporting Information File 1).…”
Section: Resultsmentioning
confidence: 79%
“…23a Another recent example is the generation of derivatives of the antibiotic elansolid via a conjugate addition of arylamines to a p -quinone methide generated under mildly basic conditions. 24 Each of these examples; the ammosamides, jadomycin and elansolid take advantage of a different reactive functional group and a different chemical transformation for analog generation, but represent a powerful approach to obtain analogs of natural products with suitable reactive intermediates.…”
Section: Resultsmentioning
confidence: 99%
“…Many substances are synthesized from the beginning of growth, or shortly after (Reinchenbach 2001). The new antibiotic scaffold elansolid exhibiting potent anti-MRSA activity (Steinmetz et al 2011(Steinmetz et al , 2012 was found in Chitinophaga sanctii, and the novel genus Aetherobacter was identified as a producer of a novel scaffold, the aetheramides, showing activity against HIV (Plaza et al 2012). Cystobacter ferrugineus was found to produce roimatacenes representing a novel class of antibiotics (Zander et al 2011), hyalidione was identified from Hyalangium minutum, and icumazoles (Barbier et al 2012) were described as a new class of antifungals from Sorangium cellulosum.…”
Section: Production Of Secondary Metabolitesmentioning
confidence: 99%